Critical Heritage Studies and the Futures of Europe - Harrison, Rodney; Dias, N. (2023)
Cultural and natural heritage are central to ‘Europe’ and ‘the European project’. They were bound up in the emergence of nation-states in the eighteenth and nineteenth centuries, where they were used to justify differences over which border conflicts were fought. Later, the idea of a ‘common European heritage’ provided a rationale for the development of the European Union. Now, the emergence of ‘new’ populist nationalisms shows how the imagined past continues to play a role in cultural and social governance, while a series of interlinked social and ecological crises are changing the ways that heritage operates, with new discourses and ontologies emerging to reconfigure heritage for the circumstances of the present and the uncertainties of the future. Taking the current role of heritage in Europe as its starting point, Critical Heritage Studies and the Futures of Europe presents a number of case studies that explore key themes in this transformation. Contributors draw on a range of disciplinary perspectives to consider, variously, the role of heritage and museums in the migration and climate ‘emergencies’; approaches to urban heritage conservation and practices of curating cities; digital and digitised heritage; the use of heritage as a therapeutic resource; and critical approaches to heritage and its management. Taken together, the chapters explore the multiple ontologies through which cultural and natural heritage have and continue to intervene actively in redrawing the futures of Europe and the world.